2017
DOI: 10.3390/coatings7110183
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Barnyard Millet Starch Films Containing Borage Seed Oil

Abstract: Abstract:In this study, barnyard millet starch (BMS) was used to prepare edible films. Antioxidant activity was conferred to the BMS film by incorporating borage seed oil (BO). The physical, optical, and thermal properties as well as antioxidant activities of the films were evaluated. The incorporation of BO into the BMS films decreased the tensile strength from 9.46 to 4.69 MPa and increased the elongation at break of the films from 82.49% to 103.87%. Water vapor permeability, water solubility, and moisture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…TS and E of the films were determined as described by Cao et al [ 42 ]. WVP of the film was determined three times at 25 °C and a RH of 50% as described by Lee et al [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TS and E of the films were determined as described by Cao et al [ 42 ]. WVP of the film was determined three times at 25 °C and a RH of 50% as described by Lee et al [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The films were dipped in 20 mL of distilled water and slightly shaken at 25 °C for 24 h. The WS was defined as the percentage of film weight loss compared to the initial weight of the film. MC of the films was determined by drying five square films (2 × 2 cm) of each sample at 105 °C for 24 h. The MC was calculated as described by Cao et al [ 42 ]. The experiment was conducted in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations were previously reported by Kadzińska et al 47 who revealed a rough lm surface structure with a heterogeneous oil droplets distribution and a tendency of cluster formation upon the incorporation of different vegetable oils including hazelnut, coconut and rapeseed oils into sodium alginate-apple puree-based lms. Likewise, Cao et al 48 observed an increase in the heterogeneity of barnyard millet starch-based lm surface upon borage seed oil incorporation due to lipid aggregates formation. A further increase in the surface roughness and heterogeneity of NaCas-based lms was noticed because of increasing both furfural and DSO concentrations with the appearance of agglomerated regions within the polymeric matrix (Fig.…”
Section: Atr-ftirmentioning
confidence: 93%
“…The amylose-rich barnyard millet starch has now attracted attention in biodegradable film making industries as an antioxidant packaging material (Cao et al, 2017). The incorporation of borage seed oil in barnyard millet starch increases the elongation range and decreases the tensile strength, water permeability, and moisture content properties of the starch, which makes it suitable for biofilm production.…”
Section: Versatile Research and Industrial Applicationsmentioning
confidence: 99%
“…The incorporation of borage seed oil in barnyard millet starch increases the elongation range and decreases the tensile strength, water permeability, and moisture content properties of the starch, which makes it suitable for biofilm production. These biofilms are found to be resistant against various microbes and block light transparency and free radical formation in food industries (Cao et al, 2017). Research on Nanoparticle by Kumar et al (2016) suggested the use of an aqueous extract from aerial parts of E. colona plant in the synthesis of silver nanoparticles (AgNPs) as a new eco-friendly approach in bio-synthesizing nanoparticle in plants.…”
Section: Versatile Research and Industrial Applicationsmentioning
confidence: 99%